Analisis Strategi Coping Stress Saat Pembelajran Online Selama Masa Pandemi Pada Siswa SMA Negeri 4 Pandeglang - Febrianti Putri Nurulita; Lina Handayani (Universitas Ahmad Dahlan, 2022)
The outbreak of the corona virus pandemic in Indonesia has prompted the government to issue a policy to implement online learning. Online learning carried out in a pandemic condition triggers stress among students. This study aims to analyze the stress coping used by students of SMA Negeri 4 Pandeglang when going online. The research method used is qualitative with a phenomenological approach. Informants in this study were students of SMA Negeri 4 Pandeglang class XI and XII who met the inclusion criteria. Based on the data that has been obtained, it is known that the stress experienced by students is triggered by various factors, including more school assignments than offline meetings, difficulty understanding school materials, unfavorable home environment, unstable internet signal and limited internet quota. Stress coping strategies that are applied by students in managing stress include coping that focuses on problems and coping that focuses on emotions. Students experience stress reactions (starin) in the form of physical and psychological reactions when faced with academic demands in online learning